Simplified Unified Model for Flexural Capacity of Ductile HPC Beams with A Low Reinforcement Ratio (Journal of Civil Engineering Researchers, 2025)
There is no specific model to predict the flexural capacity of ultra-high-performance concrete (UHPC) beams with a low reinforcement ratio. Accordingly, a comprehensive experimental database containing 162 datasets was gathered from literature to propose an explicit analytical model containing various critical features, including fiber volume fraction, fiber aspect ratio, fiber strength, water-to-binder () ratio of mixture, and reinforcement ratio. Additionally, a supplementary experimental study involving a large-scale UHPC beam with a very low reinforcement ratio (almost negligible) was conducted to verify the model's performance. The findings revealed that the proposed bending model achieved an IAE of 10.8% and a COV of 1.04, indicating its high accuracy in comparison to a comprehensive experimental dataset comprising 162 large-scale beam tests. Furthermore, the comparison between the experimental results of the tested beam and the proposed model showed a deviation of 4.5%, which supports the effectiveness of the flexural capacity formulation. A parametric statistical analysis was conducted using Minitab software to evaluate the influence of key parameters affecting the roles of fiber and matrix.
Keywords: Beam; HPC; Flexural Capacity; Low Reinforcement Ratio; Fiber Role